Improving Oil Well Cement Slurry Performance Using Hydroxypropylmethylcellulose Polymer - Abbas, Ghulam ((2013) Trans Tech Publications, Switzerland, 2013)
At present, high temperature oil wells are known as the most problematic for cementing operation due to limitations of polymer. The polymers are significantly used as mutlifunctional additives for improving the properties of cement slurry. At high temperature, viscosity of polymer decreases and unable to obtained desired properties of cement slurry. It becomes then major cause of fluid loss and gas migration during cementing operations. Thus, it necessitates for polymers that can able to enhance viscosity of slurry at elevated temperatures. This paper is aiming to study Hydroxypropylmethylcellulose (HPMC) polymer at high temperature that is able to increase the viscosity at elevated temperature. In response, experiments were conducted to characterize rheological properties of HPMC at different temperatures (30 to 100 0C). Then it was incorporated as multifunctional additive in cement slurry for determining API properties (fluid loss, free water, thickening time and compressive strength). It was observed that HPMC polymer has remarkable rheological properties that can have higher viscosity with respect to high temperatures. The best concentration of HPMC was found from 0.30 to 0.50 gallon per sack. This concentration showed minimal fluid loss, zero free water, high compressive strength and wide range of thickening time in cement slurry. The results signified that HPMC polymer is becoming multifunctional additive in cement slurry to improve the API properties of cement slurry and unlock high temperature oil wells for cementing operations.